Pengaruh Model Pembelajaran Problem Based Learning Terhadap Keterampilan Berpikir Kritis Siswa Pada Pembelajaran Tematik Terpadu Di Kelas V SDN percobaan padang - vivi puspita; Rifa Gusmihelpi (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2022)
This research is motivated by the low critical thinking skills of students due to the learning provided by the teacher has not helped students in solving problems, students' critical thinking skills in solving problems seem to be still poorly trained, the teacher only gives individual assignments and does not give group assignments, students are still less active. while studying. This study aims to determine the effect of the Problem Based Learning learning model on students' critical thinking skills in integrated thematic learning in class V SDN Experiment Padang. The subjects of this study were students of class V SDN Experiment Padang where class B as the experimental class used the Problem Based Learning learning model and class A as the control class using conventional learning, with a research design of Posttest Only Control Design. Collecting data in this study is to use a test in the form of essay questions as many as 10 items, the data obtained were analyzed using the t test. Based on the results of this study, it can be seen that t_count = 3.205> t_table = 1.67412 and a significant level of 5%. Based on the test t_count = 3.205> t_table = 1.67412 then the hypothesis or H1 is accepted. And the results of this study show that the Problem Based Learning learning model has an influence on students' critical thinking skills in integrated thematic learning in class V SDN Experiment Padang in the academic year 2021/2022. This is a new author guidelines and article template of AL-HIKMAH. Article should be started by Title of Article followed by Authors Name and Affiliation Address and abstract. This abstract section should be typed in Book Antiqua and font size of 11 pt and number of words around of 150-200. Special for the abstract section, please use left margin of 35 mm, top margin of 35 mm, right and bottom margins of 35 mm. The single spacing should be used between lines in this article. If article is written in Indonesian, the abstract should be typed in English and Indonesian. Meanwhile, if article is written in English, the abstract should be typed in English only. The abstract should be typed as concise as possible and should be composed of: problem statement, method, scientific finding results, and short conclusion. The abstract should only be typed in one paragraph and one-column format.